ECOSPARK: IGNITING COMMUNITY INNOVATION FOR A GREENER TOMORROW - Muhammad Abdurrahman, Munir; Rafeah, Wahi; Nor Hisam, Zamakshshari (2025)
ECOSPARK is a student-led initiative under the STK2983 Waste Management and Toxicology course, guided by the SULAM (Service-Learning Malaysia) framework and Kolb’s Experiential Learning Theory. Conducted over 14 weeks, the project involved 102 students collaborating with key community groups in Kota Samarahan, market vendors, the local authority (MPKS), village residents, and kindergartens, to develop sustainable waste management solutions. Core activities included composting demonstrations using on-site machines at Pusat Hijau Komuniti, interactive waste segregation workshops, and the creative “Ecoglow” art installations from recycled plastic bottles to engage young learners. Students also performed household waste audits and designed customized waste reduction strategies for villages such as Kampung Tambirat. These hands-on experiences enabled students to apply theoretical knowledge in real contexts, fulfilling Course Learning Outcome 4 (CLO4): proposing waste management projects through community engagement. The initiative contributed to Sustainable Development Goals 11 (Sustainable Cities and Communities) and 12 (Responsible Consumption and Production) while cultivating environmental responsibility, leadership, communication, and problem-solving skills among students. ECOSPARK illustrates how experiential learning and community-campus partnerships can drive environmental innovation and create lasting social impact.